Quantitative autistic traits ascertained in a national survey of 22 529 Japanese schoolchildren. (22nd November 2012) - Kamio, Y.; Inada, N.; Moriwaki, A.; Kuroda, M.; Koyama, T.; Tsujii, H.; Kawakubo, Y.; Kuwabara, H.; Tsuchiya, K. J.; Uno, Y.; Constantino, J. N.
<x xml:space="preserve">Abstract</x> Objective Recent epidemiologic studies worldwide have documented a rise in prevalence rates for autism spectrum disorders (ASD). Broadening of diagnostic criteria for ASD may be a major contributor to the rise in prevalence, particularly if superimposed on an underlying continuous distribution of autistic traits. This study sought to determine the nature of the population distribution of autistic traits using a quantitative trait measure in a large national population sample of children. Method The Japanese version of the Social Responsiveness Scale (SRS) was completed by parents on a nationally representative sample of 22 529 children, age 6–15. Results Social Responsiveness Scale scores exhibited a skewed normal distribution in the Japanese population with a single‐factor structure and no significant relation to IQ within the normal intellectual range. There was no evidence of a natural 'cutoff' that would differentiate populations of categorically affected children from unaffected children. Conclusion This study provides evidence of the continuous nature of autistic symptoms measured by the SRS, a validated quantitative trait measure. The findings reveal how paradigms for diagnosis that rest on arbitrarily imposed categorical cutoffs can result in substantial variation in prevalence estimation, especially when measurements used for case assignment are not standardized for a given population.